Journalism cupcakes: Same cakes, different icing or vice-versa - Ismail, Awan; Aripin, Norizah; Yusof, Norhafezah; Mohamad, Noraihan; Ismail, Rizalawati (University of Padjajaran, 2014)
Journalism is not a new field of studies in Malaysia. Since it was officially introduced in 1972, jounalism studies had become one of the popular courses under mass communication. Today, journalism has been offered by most of the universities in Malaysia. After three to four years of study, journalism graduates from these universities would have to share the same pie to find jobs in media or communication related organizations. But do they share the same knowledge, skills and practices from their respective universities? What differ journalism studies in one university to the other universities? Therefore, this paper attempts to examine the journalism curriculum in 9 public universities and 10 private universities in Malaysia. The specific objectives of the study are (a) to find out the major journalism subjects taught in the universities and (b) to explore the differences and or similarities of the same subjects taught by different universities. This study employs a quantitative content analysis on journalism curriculum where the selected courses’ outlines or syllabuses from different universities were taken as the unit of analysis. Most of the subjects offered are using almost the same course title but different in content and the depth or vice-versa.